Composting for Biocontained Cattle Mortality Disposal and Associated Greenhouse Gas and Leachate Emissions. Issue 2 (1st March 2016) - Gilroyed, Brandon H.; Conrad, Cheyenne; Hao, Xiying; McAllister, Tim A.; Stanford, Kim; Reuter, Tim
Abstract : Composting can be an effective means of biodegrading livestock mortalities in emergency disposal situations, such as disease outbreaks. Within the past decade, our knowledge detailing composting has increased substantially. However, research data linking the environmental impact of composting to atmospheric and terrestrial systems are limited. We investigated composting efficacy, greenhouse gas emissions, and leachate properties from two static compost piles, each containing 16 cattle mortalities, built with either beef manure (BM) or wood shavings (WS) as envelope material. Wood shavings achieved a greater maximum temperature than BM (60 vs. 50°C) and maintained higher temperatures over 200 d ( p < 0.001). Greenhouse gas emissions were evaluated using a static chamber and gas chromatography. Emissions of N2 O ( p < 0.001), CH4 ( p < 0.01), and CO2 ( p < 0.05) were lower from WS than BM, resulting in 3‐fold lower total CO2 equivalent emissions. After 250 d of composting, piles were relocated, and soil cores were taken (i) from beneath the piles, (ii) adjacent to the piles where leachate had accumulated, and (iii) in a control zone without compost exposure. Elevated concentrations of ammonium ( p < 0.05) and chloride ( p < 0.05) were found in soil beneath both BM and WS. Microbial DNA profiles suggested that leachate from BM compost increased bacterial diversity in soil, maintaining a biological soil impact after pile removal. Degradation of bovine mitochondrial DNA fragments was monitored by polymerase chain reaction. Limited migration of genetic bovine material from compost into soil was observed. Based on the mortalities decomposition and leachate contents, both BM and WS are suitable envelope materials for composting. Core Ideas: Mortality composting limits environmental emission of unwanted substances tested. Greenhouse gases are significantly lower with wood shaving as envelopment versus manure. DNA fingerprints in soil show increased bacterial and gene diversity from compost leachate.